Determinants of dividend policy for public listed companies in Malaysia - Ismail, Suhaiza (s.n, 2012)
The present study aims to examine factors affecting dividend policy of public listed firm in Malaysia.In this study that are pooled effect model, fixed effect model and random effect were analysed. The study discovered that the robust of fixed effect model is the best model to explain the objective of this study